Peningkatan Pemahaman Kecerdasan Buatan (AI) untuk Dakwah Bagi Remaja Masjid Kresen Bantul - Hamzah, Amir; Joko Basuki, Untung; Santosa, Gatot (Yayasan Kajian Riset dan Pengembangan RADISI, 2024)
Today's millennial generation faces the challenge of information technology and artificial intelligence technology that is increasingly creative in creating its applications. Artificial intelligence applications, both text-based and video-based, have the opportunity to be used in supporting da'wah for the younger generation. Teenagers of Masjid Al Aman Kresen Bantul need an increased understanding of AI technology for the development of da'wah in the millennial era. To answer this need, the community service team from IST AKPRIND created a short training program on the use of AI-based applications to support da'wah for adolescents. The materials offered are a text-based application, ChatGPT and a video-based application, HeyGen. The ChatGPT application is used to find references for da'wah materials, while the HeyGen application is to package da'wah content to make it more interesting. The training was attended by all 25 members of the AL Aman mosque teenagers. Evaluation is done through questionnaires. The evaluation results showed that 87,4% of participants considered this training very useful to increase their knowledge.